A7.10 Genetic Variants in the IL-4 and IL-4 Receptor Genes in Association with the Severity of Joint Damage in Rheumatoid Arthritis: A Study in Seven Cohorts. (25th February 2013) - Krabben, A; Wilson, AG; Rooy, DPC de; Zhernakova, A; Brouwer, E; Lindqvist, E; Saxne, T; Stoeken, G; Nies, JAB van; Knevel, R; Huizinga, TWJ; Koeleman, B; et al.
Abstract : Objective: The progression of joint destruction in rheumatoid arthritis (RA) is determined by genetic factors. Changes in IL-4 and IL-4R genes have been associated with RA severity but not replicated. We studied the association between IL-4 and IL-4R tagging SNPs and progression rate of joint damage in RA in a multi-cohort candidate gene study. Methods: IL-4 and IL-4R tagging SNPs (8 and 39, respectively) were genotyped in 600 RA-patients of whom 2, 846 sets of hands and feet X-rays were collected during 7 years follow-up. Subsequently, significantly associated SNPs were genotyped and studied in relation to 3, 415 X-rays of 1, 953 RA-patients; these included data-sets from Groningen (NL), Lund (SE), Sheffield (UK), NARAC (USA), Wichita (USA) and NDB (USA). The relative increase in progression rate per year in the presence of a genotype was determined in each cohort. An inverse variance weighting meta-analysis was done on the six datasets that together formed the replication-phase. Results: In the discovery-phase none of the IL-4 SNPs and seven of the IL-4R SNPs were significantly associated with joint damage progression rate. In the replication-phase, two SNPs in IL-4R gene were significantly associated with joint damage progression rate (Rs1805011, p = 0.02 and Rs1119132, p = 0.001). Conclusions: Genetic variants in IL-4R were identified and independently replicated to associate with progression rate of joint damage in RA.